A mediação da informação como artefato de empoderamento e resistência à violência doméstica - Carvalho, Marília Albernaz Pinheiro de (2020)
It emphasizes that domestic violence against women is a cross-cutting, multifarious phenomenon that permeates social classes, religion, race / ethnicity, faixa etária and remains, for two years, as a violation of two direct human beings. Social and cultural conditions are applied to alicerça practice that allocate to the women position of inferiority in society, naturalizing the aggressions and crimes committed by homens with which women establish relationships of affection. Evidence of mediation gives information as an artifact of empowerment not process of confrontation and break with the situation of violence. Drawing to the following research question: on the prism of the Information Science, as the mediated information we find the group formed by women victims of violence that can contribute to the process of resignificance of social conditioning factors enforced at the inferiority of women, in order to empower or confront violence and empowerment of women? Starting from the question-problem, or general objective of the investigation consisting of: analyzing, on the basis of the Information Science, the dynamics of domestic violence against women and as mediated information we find a group formed by women who are victims of domestic violence, Committed to the members of the Reflecting Project, we can contribute to the non-process of resignification of social conditions alienated to feminine inferiority, with a view to potentiating or confronting violence and social leadership of women. It uses a qualitative approach of the research-ação e item type as a research field or Operational Support Center (CAO) às Promotorias da Cidadania e Direitos Fundamentais, located in the municipality of João Pessoa - Paraíba. A demonstration of the compost of women in a situation of domestic violence committed by companions and (ex) companions, members of Projeto Refletir. The queue uses two pieces of research techniques and instruments, namely: participant observation, semi-structured interview, dynamics and focus group. To analyze the material obtained and delineate the categories, refer to the analysis of content by Laurence Bardin (2002). Respecting the limits of the research, it was found that mediation of information made it possible to problematize hegemonic gender patterns and contributed to the process of transformation, resistance and denaturalization of domestic violence, impacting the process of coping with violence and the empowerment of women. women. The research explains the power of information, knowledge and the importance of strengthening, within the scope of Information Science, studies, dialogical and reflective spaces on the issue, a serious violation of human rights, which must happen based on the view of the complexity that permeates the construction of these rights and the citizen affirmation.